2014
DOI: 10.5505/tjb.2014.27147
|View full text |Cite
|
Sign up to set email alerts
|

SERUM LIPIDS AND Lp-PLA2 ACTIVITY IN MULTIPLE SCLEROSIS

Abstract: Objective: Multiple sclerosis (MS) is an inflammatory demyelinating disease arising from unknown origin. Dyslipidemia, T-lymphocyte mediated inflammation, lipoprotein associated oxidative activity and lipoprotein associated phospholipase A2 (Lp-PLA2) activity include the pathogenesis of MS. In the current study, we evaluated the effect of Lp-PLA2 activity and serum lipids in MS patients with different clinical stages to understand the effect these parameters on MS progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…The mean plasma HDL-C and LDL-C levels of patients with MS were not statistically different from the values of the controls. Dogan (17) evaluated the effect of lipoprotein-associated phospholipase A2 (Lp-PLA2) activity and serum lipids in patients with MS. Their findings revealed that the serum lipid concentrations and Lp-PLA2 activity had no significant effect on MS and its progression. There were no statistically significant differences between patients with MS and healthy controls in terms of Lp-PLA2 activity, TChol, TG, HDL-C, LDL-C, atherogenic index of plasma (AIP), non-HDL-C and TChol to HDL-C ratio.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean plasma HDL-C and LDL-C levels of patients with MS were not statistically different from the values of the controls. Dogan (17) evaluated the effect of lipoprotein-associated phospholipase A2 (Lp-PLA2) activity and serum lipids in patients with MS. Their findings revealed that the serum lipid concentrations and Lp-PLA2 activity had no significant effect on MS and its progression. There were no statistically significant differences between patients with MS and healthy controls in terms of Lp-PLA2 activity, TChol, TG, HDL-C, LDL-C, atherogenic index of plasma (AIP), non-HDL-C and TChol to HDL-C ratio.…”
Section: Summary Of Main Findingsmentioning
confidence: 99%
“…Despite the chronic inflammatory character of MS, it is still unclear if and how lipoprotein levels are altered in patients with MS, and whether changes in feeding habits and body composition influence disease progression. This topic has been investigated in many studies in the literature (10,11,12,13,14,15,16,17,18). Weinstock-Guttman et al (10) investigated the associations of serum lipid profile variables [triglycerides (TG), high and lowdensity lipoproteins (HDL, LDL), and total cholesterol (TChol)] with disability and magnetic resonance imaging measurements in MS.…”
Section: Introductionmentioning
confidence: 99%